The beginnings of prefabricated housing construction in Belgrade (1947–1951). Contribution made by the design bureau of the Executive Committee of the People’s Committee of Belgrade - Bankovic, Angelina; Đukanović, Ljiljana (Arhitektura i urbanizam, 2026)
This paper presents and discusses the first prefabricated and semi-prefabricated residential buildings designed by the Design Bureau of the Executive Committee of the People's Committee of Belgrade during the implementation of the First Five-Year Plan (1947–1951). One of the primary objectives of the plan was to construct mass housing, which would provide much-needed accommodation for the rapidly growing population of Belgrade, liberated from occupation. Although this period has been insufficiently studied and often criticized in previous research, it was during this time that the concepts of prefabricated housing and prefabrication in general were formulated. They further developed in the following decades and significantly influenced the modernization of domestic construction practice. The idea of ​​prefabricated housing was based on the difficult-to-achieve goals regarding the number of residential square meters that had to be built, set by the First Five-Year Plan. Therefore, the paper briefly discusses the circumstances of residential construction in the given period, as well as the development of the idea of ​​prefabricated housing. Further, it presents and analyzes prefabricated and semi-prefabricated buildings that were designed and built at several locations in Belgrade under the jurisdiction of the city authorities. This paper is based on the research of available archival materials, data from the daily press, previously published papers, and field work. Its goal is to shed light on an insufficiently studied period in the history of residential architecture in Belgrade, as well as to offer a new perspective on the architectural and construction aspirations of the first post-war years.
Keywords: Belgrade; residential architecture; prefabricated and semi-prefabricated housing construction; Design Bureau of the Executive Committee of the People's Committee of Belgrade,; First Five-Year Development Plan